Overexpression of a citrus NDR1 ortholog increases disease resistance in Arabidopsis - Lu, Hua; Zhang, Chong; Albrecht, Ute; Shimizu, Rena; Wang, guanfeng; Bowman, Kim (Frontiers in Plant Science, 2013)
Emerging devastating diseases, such as Huanglongbing (HLB) and citrus canker, have caused tremendous losses to the citrus industry worldwide. Genetic engineering is a powerful approach that could allow us to increase citrus resistance against these diseases. The key to the success of this approach relies on a thorough understanding of defense mechanisms of citrus. Studies of Arabidopsis and other plants have provided a framework for us to better understand defense mechanisms of citrus. Salicylic acid (SA) is a key signaling molecule involved in basal defense and resistance (R)-gene mediated defense against broad-spectrum pathogens. The Arabidopsis gene NDR1 is a positive regulator of SA accumulation and is specifically required for signaling mediated by a subset of R genes upon recognition of their cognate pathogen effectors. Our bioinformatic analysis identified an ortholog of NDR1 from citrus, ctNDR1. Overexpression of ctNDR1 complemented susceptibility conferred by the Arabidopsis ndr1-1 mutant to Pseudomonas syringae strains and also led to enhanced resistance to an oomycete pathogen Hyaloperonospora arabidopsidis. Such heightened resistance is associated with increased SA production and expression of the defense marker gene PR1. In addition, we found that expression of PR1 and accumulation of SA were induced to modest levels in citrus infected with Candidatus Liberibacter asiaticus, the bacterial pathogen associated with HLB disease. Thus, our data suggest that ctNDR1 is a functional ortholog of Arabidopsis NDR1. Since Ca. L. asiaticus infection only activates modest levels of defense responses in citrus, we propose that genetically increasing SA/NDR1-mediated pathways could potentially lead to enhanced resistance against HLB, citrus canker, and other destructive diseases challenging global citrus production.